The importance of meteorological variation on PPP positioning - Aykut, Nedim Onur (ELSEVIER SCI LTD, 2018)
The Precise Point Positioning (PPP) technique has been used in many engineering applications. After using online PPP web services, researchers have increasingly taken the opportunity to study this technique. PPP is a positioning technique aimed at processing measurements from a single GNSS receiver in order to compute a highly accurate position in a global reference frame. The purpose of this study is to determine the effects of meteorological variations on the accuracy of PPP positioning. The Canadian Spatial Reference System (CSRS) - one of the most popular online web services - was selected for processing data from 36 observation days in 2014 acquired from the YLDZ reference station. Furthermore, the meteorological data was considered in conjunction with GNSS data processing results. Based on the analysis, RMS and coordinate differences were determined and examined. The meteorological data variations should be used for improving PPP positioning accuracy.
Keywords: GNSS/GPS; PPP; RMS; Meteorological; Seasonal; GPS; ACCURACY; GLONASS; Engineering; Instruments & Instrumentation